1985
DOI: 10.1083/jcb.100.3.955
|View full text |Cite
|
Sign up to set email alerts
|

Defective temporal and spatial control of flagellar assembly in a mutant of Chlamydomonas reinhardtii with variable flagellar number.

Abstract: Wild-type Chlamydomonas reinhardtii carry two flagella per cell that are used for both motility and mating. We describe a mutant, vfl-1, in which the biflagellate state is disrupted such that the number of flagella per cell ranges from 0 to as many as 10. vfl-1 cells possess the novel ability to assemble new flagella throughout the G1 portion of the cell cycle, resulting in an average increase of about 0.05 flagella per cell per hour. Such uncoupling of the flagellar assembly cycle from the cell cycle is not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 14 publications
2
55
0
Order By: Relevance
“…Mispositioned or absent s-and d-fibers would probably result in a mispositioning of the microtubular roots. This is the case in vfl1 mutants, in which the normal cruciate array of microtubular flagellar roots has not been observed (Adams et al, 1985). In vfl1 mutants, cell motility is also severely impaired, with even biflagellate cells showing aberrant spinning or tumbling movements, indicating that the flagella do not beat in opposite directions (Adams et al, 1985).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Mispositioned or absent s-and d-fibers would probably result in a mispositioning of the microtubular roots. This is the case in vfl1 mutants, in which the normal cruciate array of microtubular flagellar roots has not been observed (Adams et al, 1985). In vfl1 mutants, cell motility is also severely impaired, with even biflagellate cells showing aberrant spinning or tumbling movements, indicating that the flagella do not beat in opposite directions (Adams et al, 1985).…”
Section: Discussionmentioning
confidence: 88%
“…In Chlamydomonas, a kinesin-II protein, FLA10p (also called KHP1), is present at the pbbs (Vashishtha et al, 1996) and VFL1p, which is located within the lumen of bbs, was also shown to be present at the pbbs (Silflow et al, 2001). In the Chlamydomonas vfl1 mutant (Adams et al, 1985), the correct rotational orientation of the bbs is impaired (Silflow et al, 2001). By careful immunogold electron microscopy, Silflow et al showed that the position of VFL1p in the basal body is rotationally asymmetric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the variable flagellar mutants, vfl1, vfl2, and vfl3 the distal striated fiber is either absent or only partially assembled (Wright et al, 1983Adams et al, 1985). The dense plate that normally is present beneath the distal striated fiber is also absent.…”
Section: Structural Consequences Of Basal Bodies Defectsmentioning
confidence: 94%
“…In particular, the variable flagella number mutant, vfl1, was observed to have pleiotropic effects on flagellar number and localization, the timing of flagellar outgrowth during the cell cycle, and the positioning of the cleavage furrow at cytokinesis. 26 Defects in the number and localization of basal bodies and in their associated striated fibers were also observed at the ultrastructural level. Silflow et al, 27 cloned the vfl1 gene that encodes a protein of 128 kDa with five leucine-rich repeat sequences near the NH 2 terminus and a large α-helical coiled-coil domain at the COOH terminus.…”
Section: Introductionmentioning
confidence: 97%